The Addition of carrageenan flour on the fondness level of sea catfish (Arius thalassinus) meatballs - Heru Sandra Nurhuda; Junianto Junianto (Journal of Aquatropica Asia, 2016)
The purpose of this study was to find out the addition amount rate of carrageenan powder to the amount of sea catfish meat to produce the most preferred fish balls. The design used was a completely randomized design (CRD) with six treatments in adding carrageenan on the number of sea catfish meat (b / b) and 20 panelists as repetition. The six treatments were 0.0%, 0.5%, 1.0%, 1.5%, 2.0%, and 2.5%. The parameters measured were the level of fondness based on the organoleptic characteristics which included appearance, aroma, texture and taste. The analysis used was nonparametric Friedman analysis, which followed by a multiple comparison test if there were differences on the treatments. The decision making was best done by using Bayes methods. The results showed that the addition rate of carrageenan powder at 1% of the sea catfish meat weight produced most preferred fish balls of other treatments